In Support of a Profession-Wide Performance Assessment for Teacher Certification: Making What Really Matters Count. Issue 4 (2nd October 2022) - Falk, Beverly
ABSTRACT: This commentary discusses New York State's recent decision to eliminate use of the edTPA, a performance assessment designed to be a profession-wide certification requirement. It first shares research supporting performance assessments as a powerful and valid means of assessing what individuals know and can do. It then argues that a common performance assessment requirement for the profession ensures that "what matters most" about the knowledge and skills needed for teaching is possessed by anyone entering the profession. The author's experiences are shared to corroborate this claim, concluding with challenges that this viewpoint presents and recommendations to programs and states using edTPA for how to address them.